Rising Nationalism and the Diminishing Role of the Christian Institutions in Chinese National Physical Education and Sport, 1919–1928. Issue 12 (13th August 2017) - Zhang, Huijie
Abstract: The May Fourth and Anti-Christian Movements represented rising tides of national in China had a significant influence on Christian institutions and the programs of physical education and sport they promoted. From 1919 to 1928, Chinese nationalists gradually took over physical education programs from the foreign Christian missionaries and YMCA directors through an indigenization process that took place through a complex negotiation between the Western and Chinese values. During this period, Christian influence was severely affected by these movements that incited the Chinese people to claim their sport sovereign rights from foreigners' hands. The role of missionary educational institutions and the YMCA in physical education and sport declined dramatically, and Western physical education and sport in China underwent a nationalizing purification. This indigenous purification process illuminates how Chinese nationalists responded to Western imperialism and the influence of the Christian institutions during the early twentieth century.